An Ethnobiology-Based Instructional Model Integrating Indigenous Papuan Knowledge: The Mediating Role of Systems Thinking in Enhancing Environmental Literacy - Dwi Yarmalinda; Muhamad Imron; Susanti Fakaubun; Yusuf K. Numberi (Yayasan Darussalam Bengkulu, 2026)
This study examined the effectiveness of an ethnobiology-based instructional model integrating Indigenous Papuan knowledge in improving environmental literacy through systems thinking. The study responds to the limited use of culturally contextualized learning models that explain the cognitive mechanisms linking Indigenous knowledge integration and environmental literacy outcomes. A design-based research approach combined with a one-group pretest–posttest quasi-experimental design was conducted with 72 third-year Biology Education students at STKIP PGRI Papua, Indonesia. The Ethnobiology–Systems Thinking Instructional Model (ESTIM-Papua) was developed through iterative design, validation, implementation, and evaluation stages. Data were collected using a 25-item environmental literacy questionnaire, systems thinking performance tasks, classroom observations, and semi-structured interviews. Quantitative data were analyzed using paired-sample t-tests, Cohen’s d, Pearson correlation, and bootstrapped mediation analysis, while qualitative data were analyzed thematically. The results showed significant improvements in environmental literacy, from M = 62.45 to M = 78.63, t = 14.27, p < .001, d = 1.68, and systems thinking, from M = 58.72 to M = 76.15, t = 15.11, p < .001, d = 1.78. Systems thinking was positively associated with environmental literacy, r = .72, p < .001, and significantly mediated the relationship between model implementation and environmental literacy (indirect effect = .38, 95% CI [.27, .51]). Qualitative findings indicated increased engagement, deeper understanding of ecological interconnections, and improved systemic environmental problem analysis. These findings suggest that integrating Indigenous Papuan knowledge into ethnobiology-based instruction can strengthen environmental literacy by developing systems thinking. However, the single-group design and context-specific sample limit generalizability; future research should employ comparative designs across multiple institutions.